Evaluation of Contrast Extravasation as a Diagnostic Criterion in the Evaluation of Arthroscopically Proven HAGL/pHAGL Lesions. (3rd November 2014) - Maldjian, Catherine; Khanna, Vineet; Bradley, James; Adam, Richard
Abstract : Purpose . The validity of preoperative MRI in diagnosing HAGL lesions is debated. Various investigations have produced mixed results with regard to the utility of MRI. The purpose of this investigation is to apply a novel method of diagnosing HAGL/pHAGL lesions by looking at contrast extravasation and to evaluate the reliability of such extravasation of contrast into an extra-articular space as a sign of HAGL/pHAGL lesion. Methods . We utilized specific criteria to define contrast extravasation. We evaluated these criteria in 12 patients with arthroscopically proven HAGL/pHAGL lesion. We also evaluated these criteria in a control group. Results . Contrast extravasation occurred in over 83% of arthroscopically positive cases. Contrast extravasation as a diagnostic criterion in the evaluation of HAGL/pHAGL lesions demonstrated a high interobserver degree of agreement. Conclusions . In conclusion, extra-articular contrast extravasation may serve as a valid and reliable sign of HAGL and pHAGL lesions, provided stringent criteria are maintained to assure that the contrast lies in an extra-articular location. In cases where extravasation is not present, the "J" sign, though nonspecific, may be the only evidence of subtle HAGL and pHAGL lesions. Level of Evidence . Level IV, Retrospective Case-Control series.